Quackbot: Robot Pengumpul Telur Bebek Menggunakan Artificial Intelligence Berbasis IoT - Mindara, Gema Parasti; Fathonah, Lathifunnisa; Novianty, Inna; Nisa, Afifah Rodhiyatun; Dewanto, Muhammad Arif Bagus; Ramadhan, Herlambang Nurasyid; Fahlevy, Annaliah (Jurnal ICT: Information Communication & Technology, 2025)
The rapid advancement of robotic technology in the digital era has significantly impacted various industries, including poultry farming. One of the challenges faced by farmers is the manual collection of eggs, which poses risks of breakage and potential fraud in egg count records by workers. To address this issue, Quackbot, an AI and Internet of Things (IoT)-based egg-fetching robot, has been developed. This robot integrates YOLOv8 as an AI model to accurately detect eggs and an IoT system that allows farmers to monitor the number of collected eggs in real-time. The development of this robot follows the HDLC method, which includes Planning, Analysis, Design, Implementation, and Maintenance. The robot is designed to move autonomously to collect eggs and return to its basecamp once it reaches maximum capacity. This system enhances efficiency, safety, and transparency in egg collection, reducing losses and increasing farm productivity.